2000
DOI: 10.1210/jc.85.2.623
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Variations in Maternal and Neonatal Thyroid Function Induced by Iodine Supplementation during Pregnancy

Abstract: Whereas the consequences of extremes in iodine intake are well described, much less is known about the effect of more moderate variations in maternal iodine intake on fetal thyroid function. The present study performed in Denmark with mild to moderate iodine deficiency dealt with the effect of maternal iodine supplementation on thyroid function in the mother at term and in the fetus/neonate. Serum was collected consecutively from pregnant women at term (n = 144) and from cord blood (n = 139). Forty-nine women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 0 publications
8
67
1
2
Order By: Relevance
“…However, in the group of hypothyroid women treated with L-thyroxine we did not show a positive influence of iodine supplementation on the foetal thyroid function parameter, which is the neonate TSH concentration. Similar results were obtained by other authors, who measured TSH concentrations in umbilical cord blood samples of children of healthy women receiving iodine supplementation in a dose of 150 μg daily [29]. Velasco et al also found an increase of neonatal TSH in a group of pregnant women receiving 50-200 μg of iodine daily, but based on psychomotor tests performed at 3-18 months of age he also showed that iodine supplementation positively influenced on the neurological development of children [30].…”
Section: Prace Oryginalnesupporting
confidence: 82%
“…However, in the group of hypothyroid women treated with L-thyroxine we did not show a positive influence of iodine supplementation on the foetal thyroid function parameter, which is the neonate TSH concentration. Similar results were obtained by other authors, who measured TSH concentrations in umbilical cord blood samples of children of healthy women receiving iodine supplementation in a dose of 150 μg daily [29]. Velasco et al also found an increase of neonatal TSH in a group of pregnant women receiving 50-200 μg of iodine daily, but based on psychomotor tests performed at 3-18 months of age he also showed that iodine supplementation positively influenced on the neurological development of children [30].…”
Section: Prace Oryginalnesupporting
confidence: 82%
“…This is a cross-sectional study carried out from November 1988 to March 1990 in five different cities in Denmark (14,24,30,31). As the time of study enrollment was before the mandatory Danish iodine fortification of salt introduced in the year 2000 (32), the population had in general mild (East Denmark) to moderate (West Denmark) iodine deficiency with the majority of the women under study living in an area of moderate iodine deficiency (78.6%).…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Treatment had no significant effect on the concentration of maternal TSH, T 3 , T 4 , Tg or on the thyroid volume, and had no effect on the concentration of TSH in the newborn 51 . In a placebo-controlled, double-blind trial, Nohr et al 52 gave to 66 pregnant women who had antibodies to antithyroid peroxidase (TPO-Ab) a multi-nutrient supplement containing 150 mg iodine per day or a placebo control from the eleventh week of pregnancy to full term. The median UI concentration was significantly higher in the treated women at full term than in the controls, but there were no differences in the concentration of maternal TSH, fT 4 or Tg between groups 52 .…”
mentioning
confidence: 99%
“…In a placebo-controlled, double-blind trial, Nohr et al 52 gave to 66 pregnant women who had antibodies to antithyroid peroxidase (TPO-Ab) a multi-nutrient supplement containing 150 mg iodine per day or a placebo control from the eleventh week of pregnancy to full term. The median UI concentration was significantly higher in the treated women at full term than in the controls, but there were no differences in the concentration of maternal TSH, fT 4 or Tg between groups 52 . There was no difference in the prevalence of anti-thyroglobulin antibodies (Tg-Ab) or TPO-Ab, and no differences between groups in the prevalence or severity of post-partum thyroid dysfunction (PPTD), defined as an abnormal TSH concentration in the ).…”
mentioning
confidence: 99%